Development of a high-affinity anti-bovine PD-1 rabbit–bovine chimeric antibody using an efficient selection and large production system - Okagawa, Tomohiro; Konnai, Satoru; Goto, Shinya; Sajiki, Yamato; Ganbaatar, Otgontuya; Watari, Kei; Nakamura, Hayato; Wang, Cai-Xia; Tachibana, Taro; Kato, Yukinari; Kameda, Yayoi; Kohara, Junko; et al. (Veterinary research (Paris), 2023)
Immune checkpoint molecules PD-1/PD-L1 cause T-cell exhaustion and contribute to disease progression in chronic infections of cattle. We established monoclonal antibodies (mAbs) that specifically inhibit the binding of bovine PD-1/PD-L1; however, conventional anti-PD-1 mAbs are not suitable as therapeutic agents because of their low binding affinity to antigen. In addition, their sensitivity for the detection of bovine PD-1 is low and their use for immunostaining PD-1 is limited. To address these issues, we established two anti-bovine PD-1 rabbit mAbs (1F10F1 and 4F5F2) and its chimeric form using bovine IgG1 (Boch1D10F1), which exhibit high binding affinity. One of the rabbit mAb 1D10F1 binds more strongly to bovine PD-1 compared with a conventional anti-PD-1 mAb (5D2) and exhibits marked inhibitory activity on the PD-1/PD-L1 interaction. In addition, PD-1 expression in bovine T cells could be detected with higher sensitivity by flow cytometry using 1D10F1. Furthermore, we established higher-producing cells of Boch1D10F1 and succeeded in the mass production of Boch1D10F1. Boch1D10F1 exhibited a similar binding affinity to bovine PD-1 and the inhibitory activity on PD-1/PD-L1 binding compared with 1D10F1. The immune activation by Boch1D10F1 was also confirmed by the enhancement of IFN-γ production. Finally, Boch1D10F1 was administered to bovine leukemia virus-infected cows to determine its antiviral effect. In conclusion, the high-affinity anti-PD-1 antibody developed in this study represents a powerful tool for detecting and inhibiting bovine PD-1 and is a candidate for PD-1-targeted immunotherapy in cattle.